Analysis of the Efficacy of the U.S. Charity Care System. Issue 3 (24th September 2013) - Raja, Junaid; Arif, Ahmed A.; Warren‐Findlow, Jan; Racine, Elizabeth F.
Abstract The Hill–Burton Act attempted to create a safety net for underprivileged Americans with the idea of "charity care." This paper explores the efficacy with which eligible hospitals accomplish this goal by calculating a benefit‐to‐cost ratio (BCR) relative to the socio‐demographic characteristics (population density, rate of poverty, and diversity) of the hospital's county. Eight states (CA, FL, GA, MN, MT, RI, TX, and WI) and 893 hospitals were included using data from 2007. A BCR of the dollars of charity care provided versus the dollars of federal tax exemption received was performed and sociodemographic characteristics were compared covariately to examine potential disparities. The study illustrates that for every dollar of exemption, the public received 0.11 of charity care. There is a statistically significant association between a higher percentage of diversity and poverty and a decrease in BCR; county level rates of poverty and diversity are negatively correlated with BCR and only 1 percent of hospitals have a cost‐effective BCR. The investment in the charity care system is providing a very low rate of return and improvements or alternatives on the national scale should be considered.